(untitled) (Islas, 2022)
This article brings together theoretical-methodological considerations related to the study of the nominal group and its nucleus. This corresponds to the need to analyze grammatical structures within communicative processes. For this, it is necessary to characterize semantically and pragmatically the nominal group based on the Royal Spanish Academy. The objective pursued is to include the semantic and pragmatic dimensions in the study of this grammatical category. This proposal is based on the principles of discourse linguistics, and the cognitive, communicative and sociocultural approach is assumed as an analysis approach.